Electronic System Solution Creation Model Efficiency - Bagdanavičius, N.; Balaišis, P.; Barysaitė, I.; Besakirskas, A.; Janaščius, G.; Žickis, A. (Elektronika ir Elektrotechnika, 2005)
A part of features of electronic devices (ED) (including electronic systems (ES)) was distinguished from their quality conception, which characterizes technical efficiency. It was shown, that this efficiency is determined by ED attributes and properties of processes inside them. The structure of indicated processes is characterized by operation algorithm. Solution creation model (SCM) is often a constituent part of this algorithm. SCM quality and efficiency descriptions were offered. SCM technical efficiency evaluation method was introduced. Essence of this method is illustrated by optimization model of ES quality index. A case was chosen, when value of optimized ES quality index is random, and it is characterized using distribution. Efficiency is evaluated considering degree by which SCM satisfies needs. Needs are defined as the maximal allowable value of purpose function. Ill. 2, bibl. 8 (in Lithuanian; Summaries in Lithuanian, English and Russian).